2010
DOI: 10.1029/2009jg001036
|View full text |Cite
|
Sign up to set email alerts
|

Controls on the production of organohalogens by phytoplankton: Effect of nitrate concentration and grazing

Abstract: [1] Using a number of laboratory culture experiments we have been able to show that trace gas release by phytoplankton is affected by changes in ambient nitrate conditions. Nutrient concentrations are fundamentally important to phytoplankton community structure and primary production, so it is important to understand if changes in nitrate levels are likely to affect metabolic processes. Recent human activities have added a large quantity of atmospheric nitrogen to the open ocean and this, in turn, will affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Thus we suggest that photochemistry and biological production likely both played a role during MSM18/3. Haptophytes correlated most significantly of the phytoplankton groups with CH 3 I and have already been shown to produce CH 3 I both in the laboratory (Itoh et al, 1997;Manley and de la Cuesta, 1997;Scarratt and Moore, 1998;Smythe-Wright et al, 2010) and in the field (Abrahamsson et al, 2004b). Correlations during MSM18/3 additionally indicate a possible involvement of dinoflagellates and chrysophytes in the production of methyl iodide ( Table 2).…”
Section: Ch 3 I and Ch 2 Imentioning
confidence: 82%
“…Thus we suggest that photochemistry and biological production likely both played a role during MSM18/3. Haptophytes correlated most significantly of the phytoplankton groups with CH 3 I and have already been shown to produce CH 3 I both in the laboratory (Itoh et al, 1997;Manley and de la Cuesta, 1997;Scarratt and Moore, 1998;Smythe-Wright et al, 2010) and in the field (Abrahamsson et al, 2004b). Correlations during MSM18/3 additionally indicate a possible involvement of dinoflagellates and chrysophytes in the production of methyl iodide ( Table 2).…”
Section: Ch 3 I and Ch 2 Imentioning
confidence: 82%
“…Marine CH 3 I is the most abundant organoiodine in the troposphere, while the very short-lived CH 2 I 2 and CH 2 ClI contribute potentially as much organic iodine (Saiz-Lopez et al, 2012). Significant amounts of halocarbons and their degradation products can be carried into the stratosphere (Solomon et al, 1994;Hossaini et al, 2010;Aschmann et al, 2011), especially in the tropical regions where surface air can be transported very rapidly into the tropical tropopause layer by tropical deep convection (Tegtmeier et al, 2012;Tegtmeier et al, 2013). The short-lived brominated and iodinated halocarbons produced in the equatorial region may hence play an important role for stratospheric halogens.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal developments in the concentrations of Chl-a, DMS, DMSP, and DMSO in each treatment are presented in Figure 3. Previous studies have shown that Chl-a concentrations generally follow the same pattern as algal cell growth (Lim et al, 2018;Smythe-Wright et al, 2010), therefore Chl-a can be considered a representative index for the density of phytoplankton. As shown in Figure 3a, the growth patterns of the phytoplankton in different treatments were similar and all exhibited a "unimodal" pattern, with their maximum values appearing on days 7-9.…”
Section: Chl-amentioning
confidence: 97%